2015
DOI: 10.1590/s0034-8910.2015049005354
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the support offered to breastfeeding by maternity hospitals

Abstract: OBJECTIVE To evaluate whether the support offered by maternity hospitals is associated with higher prevalences of exclusive and predominant breastfeeding.METHODS This is a cross-sectional study including a representative sample of 916 infants less than six months who were born in maternity hospitals, in Ribeirao Preto, Sao Paulo, Southeastern Brazil, 2011. The maternity hospitals were evaluated in relation to their fulfillment of the Ten Steps to Successful Breastfeeding. Data were collected regarding breastfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
11
0
2
Order By: Relevance
“…We found that exclusive breastfeeding was more common in infants who did not use a pacifier and this agreed with previous research that showed that not using a pacifier in infants who were younger than six months increased both exclusive and predominant breastfeeding (27). Our results further showed that it was more common for infants who bed-shared with their parents to be exclusively or at least partially breastfed.…”
Section: Discussionsupporting
confidence: 92%
“…We found that exclusive breastfeeding was more common in infants who did not use a pacifier and this agreed with previous research that showed that not using a pacifier in infants who were younger than six months increased both exclusive and predominant breastfeeding (27). Our results further showed that it was more common for infants who bed-shared with their parents to be exclusively or at least partially breastfed.…”
Section: Discussionsupporting
confidence: 92%
“…All the practices assessed are, to some extent, included in the BFHI Ten Steps. Thus, this study corroborates previous investigations that have shown a positive impact of the BFHI on breastfeeding indicators (Braun et al, ; Coutinho, Lima Mde, Ashworth, & Lira, ; de Oliveira, Camacho, & Tedstone, ; Lamounier et al, ; Passanha, Benicio, Venancio, & Reis, ; Perez‐Escamilla, Martinez, & Segura‐Perez, ; Venancio, Saldiva, Escuder, & Giugliani, ). This impact has already been demonstrated also in the city where the present study was carried out (Braun et al, ) and in Brazil as a whole (Venancio, Saldiva, Escuder, & Giugliani, ).…”
Section: Discussionsupporting
confidence: 92%
“…The use of medications in the immediate postpartum period is very common, occurring in almost all postpartum women 1 , which may be a reason for not breastfeeding. The World Health Organization (WHO) recommends breastfeeding for at least 2 years of age and exclusively until the sixth month 2 , as breastfeeding is related to several nutritional, immunological, cognitive, psycho-affective, economic and social advantages 3 , but breastfeeding time in Brazil and in several other countries does not meet this recommendation 4 . According to Victora et al 5 , if breastfeeding was extended to an almost universal level, it could prevent 823,000 deaths of children under 5 years each year and 20,000 deaths from breast cancer, with the additional benefit of saving 300 billion dollars.…”
Section: Introductionmentioning
confidence: 99%